Stimulating Students’ HOTS Through “Striking” Digital Media in EFL Classroom - Restu Pamungkas, Nailul Author; Wulandari, Lutfina Tarita (Universitas Islam Negeri Raden Intan Lampung, 2020)
It is believed that there will always be a relationship between writing and critical thinking/HOTS. Writing is considered a process of doing critical thinking and a product that communicates the result of critical thinking. Therefore, this paper has two primary aims: first, to investigate the importance of writing and HOTS in foreign language learning; and second, to explore how those two issues can be accommodated through a single computer-assisted learning media, namely STRIKING (Strengthening Critical Thinking in Writing). The media will be in the form of a digital study package which is expected to give some benefits such as facilitating learner-centered learning, allowing the users to organize, analyze, interpret, and evaluate their own work, and getting the learners to be used to control their own learning.